DETECTING AND RESOLVING MULTICAST TRAFFIC PERFORMANCE ISSUES (2017)
The subject disclosure relates to systems and methods for improving multicast traffic flows in a computer network. In some aspects, a method of the technology includes steps for receiving multicast traffic statistics from each of a plurality of switches in a computer network, aggregating the multicast traffic statistics into a time-series database, and identifying a low-performing multicast flow based on the time-series database. In some aspects, the method can include steps for automatically reconfiguring the computer network to improve the low-performing multicast flow. Systems and machine readable media are also provided.